Analysis of unemployment among young people in Cúcuta (2021)
This document seeks to analyze the unemployment rate and the growth of poverty that have been occurring in an accelerated way in the young people of Cucuta and increasing the inequality gaps in the period 2016-2017, the consequences that student dropout brings in basic education middle and higher, gender inequality and the lack of opportunities to guarantee professional development for young people in the city that encourages them to stay in the educational cloisters through the creation of Public Policies. Additionally, this document examines the impact of the continuous migratory situation in the capital of Norte de Santander because it is a border city and the economic consequences that are evidenced by depending on the decisions made by the Colombian and Venezuelan governments.